The temporal response to drought in a Mediterranean evergreen tree: comparing a regional precipitation gradient and a throughfall exclusion experiment - Martin-StPaul, Nicolas K.; Limousin, Jean-Marc; Vogt-Schilb, Helene; Rodriguez-Calcerrada, Jesus; Rambal, Serge; Longepierre, Damien; Misson, Laurent (GLOBAL CHANGE BIOLOGY, 2013)
Like many midlatitude ecosystems, Mediterranean forests will suffer longer and more intense droughts with the ongoing climate change. The responses to drought in long-lived trees differ depending on the time scale considered, and short-term responses are currently better understood than longer term acclimation. We assessed the temporal changes in trees facing a chronic reduction in water availability by comparing leaf-scale physiological traits, branch-scale hydraulic traits, and stand-scale biomass partitioning in the evergreen Quercus ilex across a regional precipitation gradient (long-term changes) and in a partial throughfall exclusion experiment (TEE, medium term changes). At the leaf scale, gas exchange, mass per unit area and nitrogen concentration showed homeostatic responses to drought as they did not change among the sites of the precipitation gradient or in the experimental treatments of the TEE. A similar homeostatic response was observed for the xylem vulnerability to cavitation at the branch scale. In contrast, the ratio of leaf area over sapwood area (LA/SA) in young branches exhibited a transient response to drought because it decreased in response to the TEE the first 4years of treatment, but did not change among the sites of the gradient. At the stand scale, leaf area index (LAI) decreased, and the ratios of stem SA to LAI and of fine root area to LAI both increased in trees subjected to throughfall exclusion and from the wettest to the driest site of the gradient. Taken together, these results suggest that acclimation to chronic drought in long-lived Q. ilex is mediated by changes in hydraulic allometry that shift progressively from low (branch) to high (stand) organizational levels, and act to maintain the leaf water potential within the range of xylem hydraulic function and leaf photosynthetic assimilation.
The following values have no corresponding Zotero field: pub-location: 111 RIVER ST, HOBOKEN 07030-5774, NJ USA publisher: WILEY-BLACKWELL
Keywords: allometry; carbon allocation; chronic stress; ecosystem manipulation; hydraulic adjustments; leaf ecophysiology; long-term drought; Quercus ilex; Water availability